Factors affecting women's acceptance of mobile retailing : A proposed model - Azlina Bujang (2017)
The mobile retailing sectors have been revolutionised through some of the fastest growing technologies as the demand on mobility and flexibility internet technology is getting higher. Consumers are getting more interested in a retailing concept that can be reached at anytime and anywhere. The main aim of this study was to investigate the factors that influence women's acceptance towards mobile retailing. This research also aimed to access the extent of information by providing empirical and theoretical evidence on women‟s acceptance attributes towards mobile retailing. A total of 486 respondents comprising of Malaysian women who have had experience in using mobile retailing in the past six months, including mobile retailers and members of women organizations in Malaysia have each completed a set of structured self-administered questionnaire that was collected via purposive sampling technique. A Structural Equation Modeling (SEM) technique was used to assess the hypothesized relationships among the variables via Analysis of Moment Structure (AMOS) program version 21. The SEM approach revealed that women consumers‟ attitude was a significant determinant of their actual behavior in using mobile retailing, whereby they viewed it positively. They were also motivated to do more business with online retailers and are more inclined to do information sharing. It was highlighted that women consumers‟ attitude towards the use of mobile retailing was impacted by disruptive attribute reachability, ubiquity, personalization, convenience and connectivity. As one of the findings of the study, a model of women acceptance factors towards mobile retailing has been proposed. It is expected that the gap in this area and additional information especially among Malaysian women context will be filled as there is now a growing body of literature that review the details on the available information as well as recognizes the importance of mobile retailing. This research sheds light on the body of knowledge by looking into women‟s acceptance of mobile retail industry in Malaysia. Therefore, this study is optimistic that by using the proposed model, retailers are able to embark into the mobile retailing sector and subsequently attracts more women consumers to use mobile retailing as a way to shop online.